Evaluasi Efektivitas Diferensiasi Kurikulum dalam Meningkatkan Prestasi Akademis Siswa di Sekolah Menengah - Baso Intang Sappaile; Mike Nurmalia Sari; Pahmi Pahmi; Ivon Mukaddamah; Mukhtar Zaini Dahlan (Departement of Mathematics Education, 2024)
The differentiation of the curriculum has become a significant topic in the field of education, particularly at the secondary school level. This research aims to evaluate the effectiveness of the implementation of differentiated curriculum and its impact on students' academic achievements. Focusing on how this approach has been applied in specific secondary schools, the study places a central emphasis on students' responses to the differentiated curriculum. Individual student characteristics, such as learning styles and levels of understanding, are also taken into account in the analysis of the effectiveness of the differentiated curriculum. This evaluation provides an in-depth understanding of the challenges and opportunities in implementing this approach at the secondary school level, with the hope of contributing to the development of more responsive and inclusive educational policies.